PENGGUNAAN GEOINT PADA OPERASI MILITER DALAM PENANGGULANGAN KKB PAPUA DENGAN OPERABILITAS PADA SISTEM K4IPP - Arifin Hutomo; Rudy A G Gultom; Susilo Adi Purwantoro (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
National defense is influenced by the development of a dynamic strategic environment. Complex and multidimensional threats including terrorism, radicalism, separatism, armed rebellion, territorial violations to cyber attacks are challenges that affect the implementation of national defense. In handling the case of the Papuan Armed Criminal Group (KKB), the TNI must use methods and technology in carrying out its operations. By applying Geospatial Intelligence (Geoint) to obtain information and combined with the Computer Communication Control Command for Observation and Reconnaissance Intelligence (C4ISR) it will facilitate the leadership in making strategic decisions on the operation